Spread of Botrytis cinerea Strains with Multiple Fungicide Resistance in German Horticulture - Rupp, Sabrina; Weber, Roland W. S.; Rieger, Daniel; Detzel, Peter; Hahn, Matthias (Frontiers in Microbiology, 2017)
Botrytis cinerea is a major plant pathogen, causing gray mold rot in a variety of cultures. Repeated fungicide applications are common but have resulted in the development of fungal populations with resistance to one or more fungicides. In this study, we have monitored fungicide resistance frequencies and the occurrence of multiple resistance in Botrytis isolates from raspberries, strawberries, grapes, stone fruits and ornamental flowers in Germany in 2010 to 2015. High frequencies of resistance to all classes of botryticides was common in all cultures, and isolates with multiple fungicide resistance represented a major part of the populations. A monitoring in a raspberry field over six seasons revealed a continuous increase in resistance frequencies and the emergence of multiresistant Botrytis strains. In a cherry orchard and a vineyard, evidence for immigration of multiresistant strains from neighboring fields was obtained. Inoculation experiments with fungicide-treated leaves in the laboratory and with strawberry plants cultivated in the greenhouse or outdoors revealed a nearly complete loss of fungicide efficacy caused by multiple resistance. B. cinerea field strains carrying multiple resistance mutations against all classes of site-specific fungicides were found to show similar fitness as sensitive field strains under laboratory conditions, based on their vegetative growth, reproduction, stress resistance, virulence and competitiveness in mixed infection experiments. Our data confirm an alarming increase in the occurrence of multiresistance in gray mold populations from different cultures, which presents a major threat to the chemical control of gray mold.